Resource management for upland areas in southeast Asia : (Food and Agriculture Organization of the United Nations and International Institute of Rural Reconstruction, 1995)
This manual covers a broad range of social and biophysical technologies used in agroforestry in Southeast Asia, from China to Papua New Guinea. Published 1995 by FAO and the International Institute of Rural Reconstruction. It has been translated into Indonesian and Thai, and adapted for the South Pacific